REAKSI PASAR MODAL ATAS PERISTIWA PENGUMUMAN PRESIDEN RI 2014 (STUDI PADA SAHAM SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA) - Jovialco Sasongko; Marlina Widiyanti; Taufik Saggaff (JEMBATAN, 2015)
This study aimed to analyze the reaction of capital market on stocks of mining sector to the political events of the announcement of Indonesia President on 22 July 2014. The population used in this study were stocks of mining companies listed on the Indonesia Stock Exchange period 15 July 2014 - 5 August 2014 as many as 40 companies and selected a sample of 28 companies, the sampling technique used was purposive sampling. Capital market reaction measured by Abnormal Return and the examination of market reaction used event study analysis techniques. The results of the study with One-Sample T Test showed a significant Abnormal Return is happening around the announcement. The study didn’t find any significant differences in average abnormal return before and after the event by using Paired Samples T Test. The implication of this research is the investor should choose wisely stocks will be invested by considering the risks that may occur, so it will still earn returns when going on an event that affects the market.Keywords: Capital Market, Event Study, Abnormal Return